2020
DOI: 10.1177/1758835920970049
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment hemoglobin level as a predictor to evaluate the efficacy of immune checkpoint inhibitors in patients with advanced non-small cell lung cancer

Abstract: Background: Targeting immune checkpoints represents an immense breakthrough in cancer therapeutics. The prognostic value of hemoglobin (Hb) has been investigated in many malignancies including non-small cell lung cancer (NSCLC). However, the prognostic impact of pretreatment Hb count for immune checkpoint inhibitors (ICIs) in advanced NSCLC patients remains unclear. Methods: A total of 310 late-stage NSCLC patients who received ICI therapies between January 2015 and March 2019 were prospectively enrolled. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
6
19
0
Order By: Relevance
“…Patients with normal Hb level receiving PD-1 inhibitor were shown to have prolonged long term benefit of 14.4months and progression time of 7.8m (p<0.05). This was in line with previous studies of NSCLC treated with ICI ( 29 , 30 ). Hypoxia is a potent barrier to effective immunotherapy in cancer treatment ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…Patients with normal Hb level receiving PD-1 inhibitor were shown to have prolonged long term benefit of 14.4months and progression time of 7.8m (p<0.05). This was in line with previous studies of NSCLC treated with ICI ( 29 , 30 ). Hypoxia is a potent barrier to effective immunotherapy in cancer treatment ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…Other peripheral blood indexes have also been proposed to be potential predictors for the effect of ICIs treatment. A recent prospective cohort study showed that normal pre-treatment level of Hbis a favorable prognostic factor for ICIs treatment in patients with advanced NSCLC (7). Furthermore, previous studies have shown that baseline level of LDH, a biomarker related to tumor burden, was associated with the poor treatment outcomes in NSCLC patients, which can also predict the prognosis of the patients treated with ICIs (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, peripheral blood biomarkers representing tumor burden or inflammation have been increasingly studied for the purpose of predicting NSCLC treatment effect. The lower pre-treatment level or post-treatment declination of those biomarkers was previously shown to associate with the higher response rate and better prognosis in the patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, most studies were based on monotherapy, and the meaningfulness of baseline values remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that IFN-γ is a vital biomarker for NSCLC patients treated with anti-PD-1 therapy. 157 Other potential biomarkers Other potential biomarkers being investigated in anti-PD-1/PD-L1 immunotherapy on NSCLC include the pretreatment haemoglobin level, 158 serum vascular endothelial growth factor (VEGF) concentration, 159 serum lactate dehydrogenase level, 160 gut microbiome composition 116 and neoantigen load. 161 Challenges for anti-PD-1/PD-L1 treatment in advanced NSCLC Currently, there are still many unresolved problems associated with the clinical use of anti-PD-1/PD-L1 therapies (Figure 2).…”
Section: Peripheral Blood-based Biomarkersmentioning
confidence: 99%